2023
DOI: 10.35848/1347-4065/acb7fd
|View full text |Cite
|
Sign up to set email alerts
|

Directivity of photoacoustically generated ultrasound from a thin tube embedded in the soft phantom

Abstract: Authors’ previous study has revealed that the acoustic resonances had non-negligible effects on the photoacoustic signal for liquid sample confined in a thin tube. This paper presents numerical and experimental studies on the effects of tube’s hardness on the directivity of the generated photoacoustic signal. Thin glass capillary and silicone tube of 1 mm in diameter were tested with a pulsed light of 637 nm in wavelength. Black ink was confined in the capillary and tube as photoacoustic sample material. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Being based on the resonance conditions inside the tube analyzed in Ref. 38, the optimum pulse width is calculated to 290 ns. The discrepancy between the theory and the peak position in Fig.…”
Section: Temporal Waveforms Of Pa Signalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Being based on the resonance conditions inside the tube analyzed in Ref. 38, the optimum pulse width is calculated to 290 ns. The discrepancy between the theory and the peak position in Fig.…”
Section: Temporal Waveforms Of Pa Signalsmentioning
confidence: 99%
“…37) Directivity characteristics of the PA signals from a glass capillary and a soft silicone tube embedded in a soft phantom using black ink as the target liquid were investigated. 38) The influence of the acoustic modes in the tubes and the elastic properties of the tube wall on the frequency response and directivity of the PA signal were clarified.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, knowledge on the rheology of blood and soft tissues is important for bio-ultrasonic investigations. [5][6][7][8][9][10][11] Besides the bio and medical fields, low viscosity liquids are promising material in advanced micro fluid technologies such as inkjet and micro-fluidics. [12][13][14][15][16][17][18][19] In this paper, we propose a new application of an EMS viscosity measurement system to extend the measurement range to a lower shear rate for low-viscosity samples.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to better diagnose and treat endometrial cancer [8][9] , it must be diagnosed and treated promptly at an early stage or before malignant lesions are present. In the early detection of endometrial cancer tumor tissue, photoacoustic imaging [10][11] can be used in combination with hysteroscopy [3] , which mainly involves laser [12][13] coupling to the light source end of the hysteroscope and entering the uterine cavity through the hysteroscopic viewing channel to excite the tumor tissue in the uterine cavity to produce ultrasound, thus detecting an ultrasound signal different from that of normal tissue and thus making a diagnosis. After literature research, no application of pulsed laser coupling [14][15] through the hysteroscopic viewing channel for early endometrial cancer detection has been found.…”
Section: Introductionmentioning
confidence: 99%